2021
DOI: 10.1101/2021.05.26.445766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental changes and metabolic reprogramming during establishment of infection and progression of Trypanosoma brucei brucei through its insect host

Abstract: Trypanosoma brucei ssp , unicellular parasites causing human and animal trypanosomiasis, are transmitted between mammals by tsetse flies. Periodic changes in variant surface glycoproteins (VSG), which form the parasite coat in the mammal, allow them to evade the host immune response. Different isolates of  T. brucei  show heterogeneity in their repertoires of VSG genes and have single nucleotide polymorphisms and indels that can impact on genome editing.  T. brucei brucei  EATRO1125 (AnTaR1 serodeme) is a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
2
6
0
Order By: Relevance
“…Upon heterodimerization, this may result in activation or dominant-negative inhibition, dependent on AC isoform composition of the tip domain and changing environmental stimuli to fine-tune cAMP levels. In agreement to the model, AC isoform diversity and non-redundancy at the flagellar tip 7 and differential expression of transcripts encoding AC isoforms in trypanosomes colonizing midgut, cardia or salivary glands 34,35 have been reported. CARP3 depletion might result in local compositional imbalance of AC isoforms possibly due to isoform-specific quantitative differences in CARP3-mediated complex stability.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Upon heterodimerization, this may result in activation or dominant-negative inhibition, dependent on AC isoform composition of the tip domain and changing environmental stimuli to fine-tune cAMP levels. In agreement to the model, AC isoform diversity and non-redundancy at the flagellar tip 7 and differential expression of transcripts encoding AC isoforms in trypanosomes colonizing midgut, cardia or salivary glands 34,35 have been reported. CARP3 depletion might result in local compositional imbalance of AC isoforms possibly due to isoform-specific quantitative differences in CARP3-mediated complex stability.…”
Section: Discussionsupporting
confidence: 78%
“…Trypanosomes shuttle between the bloodstream and tissues of a mammalian host and the alimentary tract and salivary glands of a tsetse fly undergoing a series of developmental transitions that result in defined adapted stages 33 . Cyclic AMP signaling was suggested to play a role in stage development due to differential expression of transcripts encoding AC isoforms in trypanosomes colonizing midgut, proventriculus or salivary glands, respectively 34,35 . During their complex journey through the insect vector, trypanosomes are in intimate contact with host tissue surfaces and have to cope with several bottlenecks 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The following lines of evidence suggest that p197 is much larger than 197 kDa. Recent sequencing of the genome of the T. b. brucei EATRO1125 strain revealed that p197 has at least 26 repeats of 175 aa (43), indicating that the molecular weight of p197 might be as large as 660 kDa. That would make it to one of the largest trypanosomal proteins known.…”
Section: Discussionmentioning
confidence: 99%
“…Its N-terminus localizes at the OMM, while the C-terminus localizes to the proximal end of the BB/ pBB (Aeschlimann et al, 2022). In addition, p197 contains a central section of 26-28 nearly identical repeats of 175-182 amino acids (Aeschlimann et al, 2022;Naguleswaran et al, 2021).…”
Section: Introductionmentioning
confidence: 99%